Assessing the Impact of the Islamic Curriculum on Child Development in Early Education - Adelia Az-zahra (Al-Banat: Journal of Early Childhood Islamic Education, 2024)
This study aims to assess the impact of the Islamic curriculum on children's development in early childhood education, with a focus on social, moral, and cognitive aspects. The Islamic curriculum applied to early childhood is designed to form a strong character foundation by integrating religious values in learning activities. The research method used is a descriptive quantitative approach with a sample of children aged 4-6 years from several Islamic educational institutions. Data were collected through questionnaires to teachers and parents as well as structured observations in the classroom environment. The results showed that children who studied with the Islamic curriculum had a higher level of social, moral, and cognitive development compared to children in the general curriculum. Social aspects such as obedience, empathy, and cooperation are seen to be stronger, while their moral understanding includes honest, fair, and responsible behavior. In addition, on the cognitive aspect, children show a greater interest in science and mathematics, which are taught in harmony with religious values. This research confirms that a faith-based curriculum not only strengthens the spiritual aspect but is also able to support academic achievement. Thus, it is recommended that the Islamic curriculum in early childhood education continue to be developed to produce a generation with strong character and knowledge